2014
DOI: 10.1002/2014jd021672
|View full text |Cite
|
Sign up to set email alerts
|

Global assessment of OMI aerosol single‐scattering albedo using ground‐based AERONET inversion

Abstract: We compare the aerosol single-scattering albedo (SSA) retrieved by the near-UV two-channel algorithm (OMAERUV) applied to the Aura/Ozone Monitoring Instrument (OMI) measurements with an equivalent inversion made by the ground-based Aerosol Robotic Network (AERONET). A recent upgrade of the OMAERUV algorithm incorporates a modified carbonaceous aerosol model, a Cloud-Aerosol Lidar with Orthogonal Polarization-based aerosol height climatology, and a robust aerosol-type identification. This paper is the first com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
153
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 133 publications
(157 citation statements)
references
References 44 publications
4
153
0
Order By: Relevance
“…Thus, aerosol models are constructed more coarsely for SSA than for FMF, and the inversion methods focus on spectral matching of AOD at 550 nm, rather than on SSAoptimized retrieval, such as the OMI aerosol retrieval algorithm using ultraviolet radiation (Torres et al, 2013;Jeong et al, 2016). Nevertheless, the ratio of GOCI V2 SSA to AERONET SSA in a ±0.03 and ±0.05 range is 47.7 and 68.0 % for land and 69.7 and 88.3 % for ocean, respectively, which is comparable to the OMI SSA presented by Jethva et al (2014).…”
Section: Validation Of Goci Yaer V2 Ae Fmf and Ssa Over Ocean And Lmentioning
confidence: 67%
“…Thus, aerosol models are constructed more coarsely for SSA than for FMF, and the inversion methods focus on spectral matching of AOD at 550 nm, rather than on SSAoptimized retrieval, such as the OMI aerosol retrieval algorithm using ultraviolet radiation (Torres et al, 2013;Jeong et al, 2016). Nevertheless, the ratio of GOCI V2 SSA to AERONET SSA in a ±0.03 and ±0.05 range is 47.7 and 68.0 % for land and 69.7 and 88.3 % for ocean, respectively, which is comparable to the OMI SSA presented by Jethva et al (2014).…”
Section: Validation Of Goci Yaer V2 Ae Fmf and Ssa Over Ocean And Lmentioning
confidence: 67%
“…Some approximations are used in the numerical inversion algorithm which produce errors named relative errors having a standard deviation of 0.01 (Dubovik et al, 2000). AERONET's SSAs are computed for favorable atmospheric conditions (AOD 440 nm > 0.4 and solar zenith angle > 45 • ) using an algorithm which performs almucantar inversions (Jethva et al, 2014). These data are used to validate remotely sensed AOD and SSA measurements.…”
Section: Aerosol Robotic Network (Aeronet)mentioning
confidence: 99%
“…The OMAERUV product has been validated on a global scale by comparing OMI-retrieved AOD and SSA with the 15 corresponding data derived from ground-based measurements of the sun-sky photometers at the AERONET sites Jethva et al, 2014). The comparison confirmed that the OMI AOD and SSA retrievals are quite reliable.…”
Section: Aaod Retrievalsmentioning
confidence: 75%